Living at the edge of an interface area in Zimbabwe: cattle owners, commodity chain and health workers' awareness, perceptions and practices on zoonoses. (December 2015) - Gadaga, B.; Etter, E.M.C.; Mukamuri, B.; Makwangudze, K.; Pfukenyi, D.; Matope, G.
Abstract Background In the great Limpopo transfrontier conservation area (GLTFCA), there is an increased interface between wildlife and domestic animals, because rural households move their cattle into the game park in search of grazing and watering resources. This creates opportunities for inter-species transmission of infectious diseases, including zoonoses like brucellosis and tuberculosis, which may also pose a health risk to the local rural communities. This study investigated the awareness, perceptions and practices on zoonoses amongst rural cattle owners, commodity chain- and health-workers in three different localities around Gonarezhou National Park (GNP), Zimbabwe, where the interface between wild and domestic animals varies. Methods A cross-sectional study was conducted in Malipati, Chikombedzi and Chiredzi that are considered to be high-, medium- and low-domestic animal-wildlife interface areas, respectively. Data was collected from cattle owners, commodity chain and health-workers using a semi-structured questionnaire. To determine the public health risk of food-borne zoonoses, their practices with regard to meat and milk consumptions, and measures they take to prevent exposure to infections were assessed. Data were analyzed using descriptive statistics and principal component analysis. Results Most respondents (52.8 %, 102/193) were cattle owners, followed by health (30.1 %, 58/193) and lastly commodity chain workers (17.1 %, 33/193). Overall 67.4 % (130/193) of the respondents were aware of zoonoses with respective 48, 81.8, and 93.1 % of cattle owners, commodity chain, and health workers, being aware. Significantly more cattle owners (P < 0.05) from medium and low interface areas were aware of zoonoses compared to those from high interface areas. All categories of respondents cited anthrax (69.2 %), rabies (57.7 %), tuberculosis (41.5 %) and brucellosis (23.9 %) as important zoonoses. About half (46.1 %; 89/193) of the respondents perceive wildlife as important reservoirs of zoonoses. High proportions 98.4 % (190/193) and 96.4 % (186/193) of the respondents indicated that they consume meat and milk, respectively. Access to game meat and milk from informal markets was closely associated with consumption of raw meat and milk. Conclusions Fewer cattle owners from a high interface area of Malipati are aware of zoonoses compared to other areas due to combined effects of limited education and other factors disadvantaging these marginalised areas. This may increase their risk of exposure to zoonoses, considering that consumption of raw meat and milk is common. Thus, awareness campaigns may reduce the public health impact of zoonoses at the interface.